The Influence of Brand Identity and Brand Trust on Purchase Intention at Politeknik LP3I Medan - Maulidina, Maulidina; Putri, Hidayah Yoanna (International Journal of Economics and Management, 2025)
The purpose of this study is to analyze the effect of brand identity and brand trust on purchase intention at Politeknik LP3I Medan. The study aims to address the problem of how branding influences students' decision-making in choosing an educational institution. Specifically, this research seeks to answer the following questions: (1) To what extent does brand identity impact students' purchase intentions? (2) How does brand trust affect students' purchase intentions? A quantitative research design was adopted, involving a survey of 100 respondents selected through random sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) via SmartPLS software. The findings indicate that brand identity and brand trust have a significant positive effect on purchase intention, with brand trust exerting a greater influence. This study contributes to the fields of brand design and educational marketing by providing insights into how branding strategies can enhance student recruitment and institutional credibility.